Qualitätsentwicklung im Unterricht – zur Rolle digitaler Medien - Eickelmann, Birgit; Schulz-Zander, Renate (Jahrbuch der Schulentwicklung. Daten, Beispiele und Perspektiven/Jahrbuch der Schulentwicklung)

Individualisieren mit digitalen Medien – ein zeitgemäßer Beitrag zur Verbesserung von Unterrichtsqualität - Eickelmann, Birgit (Unterrichtsqualität sichern – Sekundarstufe)

Unterricht individualisieren – mit Computer und Internet - Eickelmann, Birgit (Unterrichtsqualität sichern – Grundschule)

Das Globale-Schule-System - eine Handlungsalternative im Distance Learning für das deutsche Auslandsschulwesen - Eickelmann, Birgit

Vorwort zum Track Integriertes Ertrags-/Risikomanagement in automatisierten Geschäftsprozessen - Müller, G.; Kundisch, Dennis; Sackmann, S.; Romeike, F.

Negotiating identities through pronouns of address in an immigrant community - Liebscher, Grit; Dailey-O’Cain, Jennifer; Müller, Mareike; Reichert, Tetyana (Pragmatics. Quarterly Publication of the International Pragmatics Association (IPrA))
This article investigates forms of address, in particular the T/V distinction in German, in conversational interviews with German-speaking immigrants to English-speaking Canada and their descendants. From among 77 interviews conducted in two urban areas in Canada, we discuss instances of both the interactional use of and metalinguistic comments on forms of address. Our analysis is largely guided by conversation analysis and interactional sociolinguistics (e.g. Goodwin & Heritage 1990). Using Clyne, Norrby and Warren’s (2009) model of address as a backdrop, we investigate the construction of group identity and group socialization through the lens of positioning theory (e.g. van Langenhove & Harré 1993; Dailey-O’Cain & Liebscher 2009). This combination of analytical tools can explain shifts in both usage of and attitudes toward the T/V distinction that cannot be explained through language attrition arguments alone.
Keywords: Forms of address; T/V distinction; Du vs. Sie; Conversation analysis; Language attitudes; Interviews; German in Canada; Migration studies; North American migration

Robust Undetectable Interference Watermarks - Grza̧ślewicz, Ryszard; Kutyłowski, Jarosław; Kutyłowski, Mirosław; Pietkiewicz, Wojciech (ICCSA'05: Proceedings of the 2005 international conference on Computational Science and Its Applications)

An investigation of doubly-resonant optical parametric oscillators and nonlinear crystals for squeezing - Stefszky, Michael; Mow-Lowry, Conor M; McKenzie, Kirk; Chua, Sheon; Buchler, Ben C; Symul, Thomas; McClelland, David E; Lam, Ping Koy (Journal of Physics B: Atomic, Molecular and Optical Physics)

Lebenszyklusorientierte Investitionsplanung - Betz, Stefan (Der Betrieb)

Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 2: Theoretical analysis of the formation mechanism - Körmer, R.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
This work investigates the mechanisms which lead to the formation of silicon nanoparticles with narrow size distributions by means of population balance modeling. The model accounts for the full aerosol process, including chemical reaction, nucleation from supersaturated vapor, growth and agglomeration. The results are in good agreement with experimental data. The effects of the process parameters temperature, silane concentration and reactor total pressure are systematically investigated. The simulation allows an in-depth insight into the particle formation mechanism and reveals the key requirements which are necessary for the generation of narrow particle size distributions. In this mechanism, only a short nucleation burst occurs, while surface growth plays the dominant role in silane precursor consumption. A key role is attributed to condensation, because the numerical calculations can only reflect the experimental observations, if the condensation mechanism is included in the model.

Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 1: Experimental investigations - Körmer, R.; Jank, M.P.M.; Ryssel, H.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
A study on the feasibility of aerosol processing of nearly monodisperse silicon nanoparticles via pyrolysis of monosilane in a hot wall reactor is presented. For optimal conditions silicon nanoparticles with a geometric standard deviation of 1.06 were synthesized at a production rate of 0.7 g/h. The size of the particles could be precisely controlled in the range of 20–40 nm, whilst maintaining a geometric standard deviation in the range of 1.06–1.08, by proper choice of the governing parameters temperature, residence time and precursor concentration. The results show that narrow particle size distributions can only be obtained in the temperature range between 900 and 1100 °C, as long as both the initial silane concentration (1 mbar silane partial pressure) and the reactor total pressure are low (25 mbar). This regime for the production of narrow particle size distributions has not been identified in prior work on the thermal decomposition of silane. Narrowly distributed particles can be obtained under conditions where nucleation and particle growth are separated and the agglomeration rates are negligible.

Interparticle forces in silica nanoparticle agglomerates - Seipenbusch, M.; Rothenbacher, S.; Kirchhoff, M.; Schmid, Hans-Joachim; Kasper, G.; Weber, A. P. (Journal of Nanoparticle Research)
To improve the understanding of the poor dispersability of fumed silica nanoparticle agglomerates, the stability of highly defined agglomerated model particles was investigated. The high temperature synthesis conditions for fumed silica were simulated by tempering. Along with electron-microscopical analysis of the sintering necks, the interparticle forces were investigated by energy resolved fragmentation analysis based on low pressure impaction. At temperatures above 1,000 °C the fragmentability of the agglomerates rapidly decreased while the energy necessary for fragmentation increased. The development of sintering necks was observed for temperatures exceeding 1,300 °C. Comparison of the experimental data with the fragmentation behaviour of a commercially produced fumed silica indicated solid state contacts (sintering necks) as being most numerous in the agglomerates resulting in limited fragmentability.

Verfahren zur integrierten informationstechnischen Unterstützung des Innovationsmanagements - Ihmels, Stephan

7. Paderborner Workshop Entwurf mechatronischer Systeme - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm; Trächtler, Ansgar

Run-time Reconfigurable Multiprocessors - Purnaprajna, Madhura

Lebensdauerüberwachung in mechatronischen Systemen - Wedman, Sebastian

6. Symposium für Vorausschau und Technologieplanung - Gausemeier, Jürgen

Systematik zur funktionsorientierten Modellierung von Elektrik/ Elektronik-Systemen über den Produktlebenszyklus - Warkentin, Andreas

Adaptable OS services for distributed reconfigurable systems on chip - Samara, Sufyan

On the design and implementation of reliable and economical telematics software architectures for embedded systems : a domain-specific framework - Stehr, Jan

Price Efficiency in Futures and Spot Trading: The Role of Information Technology - Wagener, Martin; Kundisch, Dennis; Riordan, R.; Rabhi, Fethi; Herrmann, Philipp; Weinhardt, C. (Electronic Commerce Research and Applications)

Characterizing nonclassicality and entanglement - Vogel, W.; Kiesel, T.; Sperling, Jan (Optics and Spectroscopy)

Customer Portfolio Management in E-Commerce - An Analytical Model for Optimization - Sackmann, S.; Kundisch, Dennis; Ruch, M. (Management Research Review)

A User-Driven SOA for Financial Market Data Analysis - Guabtni, A.; Kundisch, Dennis; Rabhi, Fethi (Enterprise Modelling and Information Systems Architectures)

Der Einfluss von Sozialkapital in der Asset Allocation von Privatanlegern - Kundisch, Dennis; Zorzi, R. (Journal of Banking and Financial Research)

Einfluss der Finanzierung auf die Steuerbarkeit und Vorteilhaftigkeit von Investitionen - Kundisch, Dennis; Satzger, G. (Der Betrieb)

Dirac point and edge states in a microwave realization of tight-binding graphene-like structures - Kuhl, U.; Barkhofen, Sonja; Tudorovskiy, T.; Stöckmann, H.-J.; Hossain, T.; de Forges de Parny, L.; Mortessagne, F. (Physical Review B)

Einführung in den Anfangsunterricht - Hellmich, Frank

Handbuch Experimentieren.

Geschlechtsspezifische Unterschiede in der Lesekompetenz bei Grundschulkindern im Zusammenhang mit pädagogisch-didaktischen Überzeugungen ihrer Lehrkräfte - Hellmich, Frank; Höntges, Jens; Günther, Frederike (Erziehungswissenschaftliche Forschung – nachhaltige Bildung)

Attributionsstile von Grundschulkindern und deren Erklärungsfaktoren - Hellmich, Frank; Günther, Frederike; Sievers, Sebastian (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik. Jahrbuch Grundschulpädagogik)

Attributionsstile von Grundschulkindern und deren Erklärungsfaktoren - Deters, Thomas; Hellmich, Frank (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik.)

Förderung der Lesefähigkeit durch Lesetagebücher – Ergebnisse aus einer empirischen Studie - Höntges, Jens; Hellmich, Frank (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik)

Wissenschaftliches Denken in der Grundschule - Hellmich, Frank; Höntges, Jens (Handbuch Experimentieren)

Glück oder Pech? Über Erfolge und Misserfolge nachdenken – eine Herausforderung für Kinder?! - Deters, Thomas; Hellmich, Frank (Grundschulunterricht)

Diagnose und Förderung im Mathematikunterricht der Grundschule - Hellmich, Frank (Anspruchsvolles Fördern in der Grundschule)

Erklärungsfaktoren für dynamische Selbstkonzepte bei Grundschulkindern - Hellmich, Frank; Günther, Frederike; Sievers, Sebastian (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik)

Validation of protein intake assessed from weighed dietary records against protein estimated from 24 h urine samples in children, adolescents and young adults participating in the Dortmund Nutritional and Longitudinally Designed (DONALD) Study - Bokhof, Beate; Günther, Anke LB; Berg-Beckhoff, Gabriele; Kroke, Anja; Buyken, Anette (Public Health Nutrition)

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

Relation of isoflavones and fiber intake in childhood to the timing of puberty - Cheng, Guo; Remer, Thomas; Prinz-Langenohl, Reinhild; Blaszkewicz, Meinolf; Degen, Gisela H; Buyken, Anette (The American Journal of Clinical Nutrition)

A CSP Approach to Control in Event-B - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Integrated Formal Methods - 8th International Conference, IFM 2010, Nancy, France, October 11-14, 2010. Proceedings)

{SLAB:} A Certifying Model Checker for Infinite-State Concurrent Systems - Dräger, Klaus; Kupriyanov, Andrey; Finkbeiner, Bernd; Wehrheim, Heike (Tools and Algorithms for the Construction and Analysis of Systems, 16th International Conference, TACAS 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings)

Towards A Shape Analysis for Graph Transformation Systems - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (CoRR)

Survival at the center—the stability of minimum differentiation - Hehenkamp, Burkhard; Wambach, Achim (Journal of Economic Behavior & Organization)

Produktivitätsbenchmarking als Bestandteil eines integrierten Ansatzes zur Vermarktung hybrider Leistungsbündel - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Broeker, Ole; Knackstedt, Ralf; Nikula, Anna; Wilken, Robert (40. Jahrestagung der Gesellschaft für Informatik)

Incorporating Willingness-to-Pay Data into Online Recommendations for Value-Added Services - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Frohs, Margarete; Müller, Oliver; Weddeling, Matthias (European Conference on Information Systems)

Produktivitätsmanagement hybrider Leistungsbündel --- Auf dem Weg zu einer Produktivitätsmanagementsystematik für effiziente Wertschöpfungspartnerschaften - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Fellmann, Michael; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver (Proceedings of the Multikonferenz Wirtschaftsinformatik)

Assumptions in Service Research --- A Multi-Theoretical Perspective on the Development of Standards for the Integration of Goods and Services - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Nüttgens, Markus (XX. International RESER Conference)

Total Cost of Service Life --- Decision Support for Selecting and Orchestrating Services - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the IADIS Internatioal Conference e-Society 2010)

Total Costs of Service Life: The Need of Decision Support in Selecting, Comparing and Orchestrating Services - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Exploring Service Sciences)